A Potential Commercial Source of Fucoxanthin Extracted from the Microalga Phaeodactylum tricornutum - Kim, Sang Min; Jung, Yu-Jin; Kwon, Oh-Nam; Cha, Kwang Hyun; Um, Byung-Hun; Chung, Donghwa; Pan, Cheol-Ho (SPRINGER, 2012)
Fucoxanthin, one of the main marine carotenoids, is abundant in macro- and microalgae. Here, fucoxanthin was isolated and structurally identified as the major carotenoid in the diatom Phaeodactylum tricornutum through chromatographic and spectroscopic methods, such as liquid chromatography-positive-ion atmospheric pressure chemical ionization/mass spectroscopy and nuclear magnetic resonance. This pigment was quantified by reverse-phase high-performance liquid chromatography, and a number of extraction procedures were assessed to investigate the effect of solvent type, extraction time, temperature, and extraction method (maceration, ultrasound-assisted extraction, Soxhlet extraction, and pressurized liquid extraction). Among the investigated solvents, ethanol provided the best fucoxanthin extraction yield (15.71 mg/g freeze-dried sample weight). Fucoxanthin content in the extracts produced by the different methods was quite constant (15.42-16.51 mg/g freeze-dried sample weight) but increased steeply based on the percentage of ethanol in water, emphasizing the importance of ethanol in the extraction. The results indicate that P. tricornutum is a rich source of fucoxanthin (at least ten times more abundant than that in macroalgae) that is easily extracted with ethanol, suggesting potential applications in human and animal food, health, and cosmetics.
Keywords: PRESSURIZED LIQUID EXTRACTION; CAROTENOID FUCOXANTHIN; PIGMENTS; SEAWEED; ALGAE